Nanometer layered y2o3-yag composite etching-resistant coating and preparation method thereof

CN122979835APending Publication Date: 2026-10-27无锡卓瓷科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611482205.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有的抗刻蚀涂层用于半导体器件制备,存在孔隙率高、与基体结合强度低,以及耐等离子体刻蚀性能不足的问题

Benefits of technology

本发明采用双源电子束物理气相沉积技术,在真空室内架设高纯Y2O3和高纯YAG两个独立蒸发坩埚,通过微机控制系统对双电子枪的发射功率与启闭时序进行闭环联动控制,在陶瓷基体表面交替沉积厚度交错的Y2O3纳米层与YAG纳米层,形成人工调制的纳米超点阵层状结构。通过周期性界面的钉扎效应显著抑制贯穿性柱状晶的纵向生长与横向晶界的连续连通,使涂层内部无任何宏观贯穿孔,显著降低了等离子体粒子的纵向渗透通道。同时,纳米层状界面处因晶格失配产生的高密度界面位错网络有效散射了高能氟基等离子体粒子,使涂层在较薄厚度的前提下,抗氟基等离子体物理化学轰击能力大幅提升,孔隙率下降,大大减少传统热喷涂涂层因微孔、裂纹缺陷导致的颗粒剥落和晶圆污染问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979835A_ABST
    Figure CN122979835A_ABST
Patent Text Reader

Abstract

The application discloses a nano-layered Y2O3-YAG composite etching-resistant coating and a preparation method thereof, and relates to the technical field of coating materials. The preparation method of the nano-layered Y2O3-YAG composite etching-resistant coating provided by the application comprises the following steps: providing a ceramic substrate; alternately and cyclically depositing nano-layered Y2O3 and nano-layered YAG on one side of the ceramic substrate to obtain the nano-layered Y2O3-YAG composite etching-resistant coating; and wherein, the nano-layered Y2O3-YAG composite etching-resistant coating is close to and far away from the side of the ceramic substrate, and is the nano-layered Y2O3. The nano-layered Y2O3-YAG composite etching-resistant coating prepared by the application effectively inhibits the growth of columnar crystals, reduces through pores, and significantly improves the etching resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating materials technology, specifically to a nano-layered Y2O3-YAG composite anti-etching coating and its preparation method. Background Technology

[0002] With the rapid development of the semiconductor industry, integrated circuit manufacturing technology is constantly advancing towards higher precision, smaller size, and more complex structures. In particular, the introduction of extreme ultraviolet (EUV) processes in photolithography has made integrated circuits with linewidths below 3nm possible. Against this backdrop, plasma etching technology, as a key micro-nano fabrication method, has become an indispensable core process in semiconductor manufacturing. Plasma etching achieves precise etching of materials using high-energy, high-density plasma, thereby improving the manufacturing efficiency and yield of integrated circuits, enabling high-efficiency production of semiconductor devices even under highly integrated conditions. However, with the increase in wafer size and device integration, plasma etching processes also face a series of technical challenges. During the etching process, high-energy plasma generated by the ionization of halogen and inert gases is used to etch the wafer surface. However, in this process, not only the wafer material is etched, but also the inner walls of the etching equipment and key components (such as the spray head, focusing ring, and base) are etched. The etching of these components can cause a series of problems, including semiconductor device contamination, decreased yield, and shortened equipment lifespan.

[0003] To improve equipment lifespan and process stability in plasma etching environments, coatings based on Y₂O₃ or Al₂O₃ have achieved effective protection against high-temperature and highly corrosive plasmas to a certain extent, and are therefore widely used in large-size semiconductor etching equipment. However, ceramic coatings prepared by traditional thermal processes generally suffer from defects such as micropores and cracks. Under long-term bombardment by high-power plasma, these structures are prone to induce particle shedding, leading to wafer surface contamination and process instability, affecting chip yield. To improve etching protection, the coating thickness often needs to be increased to hundreds of micrometers, resulting in a significant increase in coating preparation costs and limiting its further application in higher-level processes. Therefore, there is an urgent need to develop a composite ceramic nanocoating system with high density, excellent electrical insulation, and strong plasma corrosion resistance to meet the higher requirements of advanced semiconductor manufacturing equipment for structural component protection performance, thereby improving overall equipment stability and process yield. Summary of the Invention

[0004] The purpose of this invention is to provide a nano-layered Y2O3-YAG composite anti-etching coating and its preparation method, thereby solving the following technical problems: Existing anti-etching coatings used in semiconductor device fabrication suffer from problems such as high porosity, low bonding strength with the substrate, and insufficient resistance to plasma etching.

[0005] The objective of this invention can be achieved through the following technical solutions: The preparation method of the nanolayered Y2O3-YAG composite anti-etching coating includes at least the following preparation steps: Provide a ceramic substrate; Nanolayered Y2O3 and nanolayered YAG are alternately and cyclically deposited on one side of the ceramic substrate to obtain a nanolayered Y2O3-YAG composite anti-etching coating. The nanolayered Y2O3-YAG composite anti-etching coating is located on the side of the coating closest to and furthest from the ceramic substrate.

[0006] As a further aspect of the present invention, the thickness of the nanolayered Y2O3-YAG composite anti-etching coating is 2-15 μm.

[0007] As a further aspect of the present invention, the thickness of the nanolayered Y2O3 is 18-22 nm.

[0008] As a further aspect of the present invention, the thickness of the nanolayered YAG is 8-12 nm.

[0009] As a further aspect of the present invention: the nanolayered Y2O3 further contains a first doping ion, and the first doping ion is at least one of zirconium ion, scandium ion or gadolinium ion.

[0010] As a further aspect of the present invention: the doping amount of the first doped ion is 2-10 at.%.

[0011] As a further aspect of the present invention: the nanolayered YAG further contains a second doped ion, and the second doped ion is at least one of magnesium ion, lutetium ion or scandium ion.

[0012] As a further aspect of the present invention: the doping amount of the second doped ion is 0.5-10 at.%.

[0013] As a further aspect of the present invention, the deposition rate of the nanolayered Y2O3 is 0.5-1.2 nm / s.

[0014] As a further aspect of the present invention, the deposition rate of the nanolayered YAG is 0.3-0.8 nm / s.

[0015] As a further aspect of the present invention: the deposition method is electron beam physical vapor deposition.

[0016] As a further aspect of the present invention: the doping method of the first doped ion and / or the second doped ion is any one of pre-alloyed evaporation source, multi-crucible co-evaporation or ion-assisted deposition.

[0017] As a further aspect of the present invention, the temperature of the ceramic substrate is 430-470℃.

[0018] As a further aspect of the present invention: the ceramic substrate is any one of alumina ceramic, aluminum nitride ceramic or silicon carbide ceramic, and the surface roughness Ra of the ceramic substrate is ≤0.05μm.

[0019] The nanolayered Y2O3-YAG composite anti-etching coating is prepared by any of the preparation methods described above.

[0020] The beneficial effects of this invention are: This invention employs dual-source electron beam physical vapor deposition (EPV) technology. Two independent evaporation crucibles, one for high-purity Y₂O₃ and the other for high-purity YAG, are set up in a vacuum chamber. A microcomputer control system performs closed-loop linkage control of the emission power and on / off timing of the dual electron guns. Alternating layers of Y₂O₃ and YAG nanolayers of varying thicknesses are deposited on the ceramic substrate surface, forming an artificially modulated nano-lattice layered structure. The pinning effect of the periodic interfaces significantly suppresses the longitudinal growth of penetrating columnar crystals and the continuous connectivity of transverse grain boundaries, resulting in a coating without any macroscopic through-holes and significantly reducing the longitudinal penetration channels of plasma particles. Simultaneously, the high-density interfacial dislocation network generated by lattice mismatch at the nanolayered interfaces effectively scatters high-energy fluorine-based plasma particles. This significantly enhances the coating's resistance to fluorine-based plasma physicochemical bombardment, even with a relatively thin coating thickness, and reduces porosity, greatly mitigating the particle detachment and wafer contamination problems caused by micropores and cracks in traditional thermal spray coatings.

[0021] This invention further densifies the coating microstructure by introducing first dopant ions such as zirconium, scandium, or gadolinium ions into the nanolayered Y₂O₃ and second dopant ions such as magnesium, lutetium, or scandium ions into the nanolayered YAG. This utilizes solid solution strengthening and lattice distortion effects to suppress the chemical reactivity of aluminum in the YAG phase in the formation of volatile AlF₃ under fluorine plasma conditions. The dopant ions and the nano-superlattice layered structure produce a synergistic strengthening effect, further reducing the coating porosity and the coating's resistance to fluorine plasma etching rate. This significantly extends the service life of key components in semiconductor etching equipment while substantially reducing coating preparation costs, meeting the stringent requirements of advanced semiconductor manufacturing for high-density, high-corrosion-resistant, and ultra-thin ceramic protective layers. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a laser confocal microscope image of the nanolayered Y2O3-YAG composite anti-etching coating prepared in Example 1 after etching for 10 hours; Figure 2 This is a laser confocal microscope image of the Y2O3 anti-etching coating prepared in Comparative Example 1 after etching for 10 hours; Figure 3 This is an atomic force microscope image of the nanolayered Y2O3-YAG composite anti-etching coating prepared in Example 1 after etching for 10 hours; Figure 4 This is an atomic force microscope image of the Y2O3 anti-etching coating prepared in Comparative Example 1 after etching for 10 hours. Detailed Implementation

[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1: The preparation method of the nanolayered Y2O3-YAG composite anti-etching coating includes the following steps: A 99.99% high-purity alumina ceramic disc with dimensions of Φ50mm×2mm was used as the ceramic substrate. Diamond polishing paste was applied in stages to achieve a surface roughness Ra=0.02μm. The substrate was then sequentially immersed in acetone, anhydrous ethanol, and deionized water, and ultrasonically cleaned for 15 minutes each at room temperature and 180W power. After removal, it was immediately dried with high-purity nitrogen and transferred to the sample stage in the vacuum deposition chamber. A background vacuum of 2×10⁻⁶ was then applied. -3 After Pa, high-purity argon gas is introduced at a flow rate of 20 sccm to maintain a chamber pressure of 0.8 Pa. A -400V pulse negative bias voltage is applied to the ceramic substrate, and argon ion bombardment etching is performed for 8 min to remove the surface oxide layer and organic contaminants, thus completing the pretreatment of the ceramic substrate. The pretreated ceramic substrate was fixed on the heated sample stage of the vacuum deposition chamber. High-purity argon gas was continuously introduced at a flow rate of 30 sccm, and the working pressure was stabilized at 0.25 Pa by adjusting the gate valve. A negative bias of -120 V was applied, and the temperature was increased to 450 °C at a rate of 5 °C / min and held for 30 min to form a uniform and stable deposition temperature field on the substrate surface. Two independent water-cooled copper crucibles were set up in the vacuum deposition chamber, each corresponding to an independent electron gun emission system. The first crucible was filled with 99.99% high-purity Y₂O₃ ceramic target, and the second crucible was filled with 99.99% high-purity YAG ceramic target. The emission ends of both electron guns were aligned with the central molten region of the target material in the corresponding crucible, and the system was controlled by a microcomputer. The system performs closed-loop linkage control of the emission power and on / off timing of the two electron guns. First, electron gun 1 is turned on to bombard the Y2O3 target. The electron gun power is stabilized at 2.5kW and the deposition rate is 0.8nm / s. When the single layer thickness reaches 20nm, gun 1 is automatically turned off. Then, electron gun 2 is immediately turned on to bombard the YAG target. The electron gun power is stabilized at 2.2kW and the deposition rate is 0.5nm / s. When the single layer thickness reaches 10nm, gun 2 is automatically turned off. This is one deposition cycle. The system alternates between these cycles for 200 cycles. Finally, electron gun 1 is turned on again to bombard the Y2O3 ceramic target. The deposition ends when the single layer thickness reaches 20nm, resulting in a nanolayered Y2O3-YAG composite anti-etching coating.

[0026] Example 2: The preparation method of the nanolayered Y2O3-YAG composite anti-etching coating includes the following steps: 99.99% high-purity Y₂O₃ powder (average particle size 1-2 μm) and 99.99% high-purity Sc₂O₃ powder (average particle size 0.8-1.5 μm) were separately placed in corundum crucibles and kept at 800℃ for 3 hours in a muffle furnace to remove adsorbed water and trace organic impurities. After cooling to room temperature in the furnace, the powders were removed and mixed with Sc₂O₃:Y₂O₃ at a molar ratio of 5:95. The mixtures were then placed in a polyurethane ball mill jar and dispersed in anhydrous ethanol (solid-liquid mass ratio 1:1.2). High-purity agate grinding balls (ball-to-material mass ratio 5:1) were used in a planetary ball mill at 300 r / min for 12 hours of continuous wet ball milling. The mixtures were then dried at 85℃ for 12 hours, lightly ground in an agate mortar, and passed through a 200-mesh standard sieve. Finally, 3% (by mass) of 5wt% [a specific chemical compound] was added. PVA aqueous solution was used as a binder. After thorough grinding and mixing, it was passed through a 100-mesh sieve and filled into a steel mold. It was then pressed at 50 MPa for 30 seconds in a hydraulic press and placed in a cold isostatic press at 200 MPa for 60 seconds to prepare a green blank. The green blank was then placed in an air atmosphere muffle furnace and heated to 600℃ at 1℃ / min and held for 2 hours to remove the binder. The temperature was then increased to 1700℃ at 3℃ / min and sintered in air atmosphere for 5 hours. Subsequently, the temperature was decreased to 1000℃ at 2℃ / min and then naturally cooled to room temperature in the furnace. The green blank was then ground with a diamond wheel and machined to the target size to obtain a Y2O3 ceramic target material with a first doping ion doping amount of 5 at.%. 99.99% high-purity YAG powder (average particle size 1-2 μm) and 99.99% high-purity MgO powder (average particle size 0.3-0.8 μm) were both dried at 800℃ for 3 hours. They were then mixed at a molar ratio of MgO:YAG = 8:100 and loaded into a polyurethane ball mill jar. Anhydrous ethanol was used as the medium (solid-liquid mass ratio 1:1.2). High-purity alumina grinding balls (ball-to-material mass ratio 5:1) were used in a planetary ball mill at 320 r / min for 15 hours of wet ball milling, followed by drying at 85℃ for 12 hours. After grinding, the powder was passed through a 200-mesh sieve and 3wt% of 5% [unspecified ingredient] was added. The PVA aqueous solution was granulated, passed through a 100-mesh sieve, and filled into a steel mold. It was then pressed at 50 MPa for 30 seconds in a hydraulic press, and placed in a cold isostatic press at 200 MPa for 60 seconds to prepare a green blank. The green blank was then placed in an air atmosphere muffle furnace and heated to 600℃ at 3℃ / min and held for 2 hours to remove the binder. The temperature was then increased to 1680℃ at 3℃ / min and sintered in air atmosphere for 4 hours. Subsequently, the temperature was decreased to 1000℃ at 2℃ / min and then naturally cooled to room temperature in the furnace. The green blank was then ground with a diamond wheel and machined to the target size to obtain a YAG ceramic target material with a doping amount of 1 at.% of the second doped ion. A ceramic substrate is provided, and the pretreatment steps for the ceramic substrate are the same as in Example 1; The pretreated ceramic substrate was fixed on the heated sample stage of the vacuum deposition chamber. High-purity argon gas was continuously introduced at a flow rate of 30 sccm. The gate valve was adjusted to stabilize the working pressure at 0.25 Pa. A negative bias of -120 V was applied, and the temperature was increased to 450 °C at a rate of 5 °C / min and held for 30 min to form a uniform and stable deposition temperature field on the substrate surface. Two independent water-cooled copper crucibles were set up in the vacuum deposition chamber, each corresponding to an independent electron gun emission system. The first crucible was filled with the Y₂O₃ ceramic target prepared with the first doped ion, and the second crucible was filled with the YAG ceramic target prepared with the second doped ion. The emission ends of both electron guns were aligned with the central molten region of the target material in the corresponding crucible. The emission of the two electron guns was controlled by a microcomputer control system. The electron power and on / off timing are controlled in a closed-loop linkage. First, electron gun 1 is turned on to bombard the Y2O3 ceramic target doped with the first dopant ion. The electron gun power is stabilized at 2.6kW and the deposition rate is 0.82nm / s. When the single layer thickness reaches 20nm, electron gun 1 is automatically turned off. Then, electron gun 2 is immediately turned on to bombard the YAG ceramic target doped with the second dopant ion. The electron gun power is stabilized at 2.3kW and the deposition rate is 0.51nm / s. When the single layer thickness reaches 10nm, electron gun 2 is automatically turned off. This is one deposition cycle. The deposition is carried out in an alternating manner for 200 cycles. Finally, electron gun 1 is turned on again to bombard the Y2O3 ceramic target doped with the first dopant ion. The deposition ends when the single layer thickness reaches 20nm, and a nano-layered Y2O3-YAG composite anti-etching coating is obtained.

[0027] Example 3: The preparation method of the nanolayered Y2O3-YAG composite anti-etching coating includes the following steps: 99.99% high-purity Y₂O₃ powder (average particle size 1-2 μm) and 99.99% high-purity monoclinic ZrO₂ powder (average particle size 0.5-1 μm) were separately placed in corundum crucibles and kept at 800℃ for 3 hours in a muffle furnace to remove adsorbed water and trace organic impurities. After cooling to room temperature in the furnace, the powders were removed and mixed with ZrO₂:Y₂O₃ at a molar ratio of 1:12. The mixture was then placed in a polyurethane ball mill jar and dispersed in anhydrous ethanol (solid-liquid mass ratio 1:1.2). High-purity zirconia grinding balls (ball-to-material mass ratio 5:1) were used in a planetary ball mill at 300 r / min for 14 hours of continuous wet ball milling. After drying at 85℃ for 12 hours, the powders were lightly ground in an agate mortar and passed through a 200-mesh standard sieve. 3% (w / w) of 5wt% (w / w) of [a specific chemical compound] was added. PVA aqueous solution was used as a binder. After thorough grinding and mixing, it was passed through a 100-mesh sieve and filled into a steel mold. It was then pressed at 50 MPa for 30 seconds in a hydraulic press and placed in a cold isostatic press at 200 MPa for 60 seconds to prepare a green blank. The green blank was then placed in an air atmosphere muffle furnace and heated to 600℃ at 1℃ / min and held for 2 hours to remove the binder. The temperature was then increased to 1720℃ at 3℃ / min and sintered in air atmosphere for 6 hours. Subsequently, the temperature was decreased to 1000℃ at 2℃ / min and then naturally cooled to room temperature in the furnace. The green blank was then ground with a diamond wheel and machined to the target size to obtain a Y2O3 ceramic target material with a first doping ion doping amount of 4 at.%. 99.99% high-purity YAG powder (average particle size 1-2 μm) and 99.99% high-purity Lu2O3 powder (average particle size 0.8-1.5 μm) were both dried at 800℃ for 3 hours. They were then mixed in a molar ratio of Lu2O3:YAG = 3:25 and loaded into a polyurethane ball mill jar. Anhydrous ethanol was used as the medium (solid-liquid mass ratio 1:1.2). High-purity alumina grinding balls (ball-to-material mass ratio 5:1) were used in a planetary ball mill at 320 r / min for 15 hours of wet ball milling, followed by drying at 85℃ for 12 hours. After grinding, the powder was passed through a 200-mesh sieve and 3wt% of 5% [unspecified ingredient] was added. The PVA aqueous solution was granulated, passed through a 100-mesh sieve, and filled into a steel mold. It was then pressed at 50 MPa for 30 seconds in a hydraulic press, and placed in a cold isostatic press at 200 MPa for 60 seconds to prepare a green blank. The green blank was then placed in an air atmosphere muffle furnace and heated to 600℃ at 3℃ / min and held for 2 hours to remove the binder. The temperature was then increased to 1700℃ at 3℃ / min and sintered in air atmosphere for 5 hours. Subsequently, the temperature was decreased to 1000℃ at 2℃ / min and then naturally cooled to room temperature in the furnace. The green blank was then ground with a diamond wheel and machined to the target size to obtain a YAG ceramic target material with a doping amount of 3 at.% of the second doped ion. A ceramic substrate is provided, and the pretreatment steps for the ceramic substrate are the same as in Example 1; The pretreated ceramic substrate was fixed on the heated sample stage of the vacuum deposition chamber. High-purity argon gas was continuously introduced at a flow rate of 30 sccm. The gate valve was adjusted to stabilize the working pressure at 0.25 Pa. A negative bias of -120 V was applied, and the temperature was increased to 450 °C at a rate of 5 °C / min and held for 30 min to form a uniform and stable deposition temperature field on the substrate surface. Two independent water-cooled copper crucibles were set up in the vacuum deposition chamber, each corresponding to an independent electron gun emission system. The first crucible was filled with the Y₂O₃ ceramic target prepared with the first doped ion, and the second crucible was filled with the YAG ceramic target prepared with the second doped ion. The emission ends of both electron guns were aligned with the central molten region of the target material in the corresponding crucible. The emission of the two electron guns was controlled by a microcomputer control system. The electron power and on / off timing are controlled in a closed-loop linkage. First, electron gun 1 is turned on to bombard the Y2O3 ceramic target doped with the first dopant ion. The electron gun power is stabilized at 2.4kW and the deposition rate is 0.78nm / s. When the single layer thickness reaches 20nm, electron gun 1 is automatically turned off. Then, electron gun 2 is immediately turned on to bombard the YAG ceramic target doped with the second dopant ion. The electron gun power is stabilized at 2.1kW and the deposition rate is 0.48nm / s. When the single layer thickness reaches 10nm, electron gun 2 is automatically turned off. This is one deposition cycle. The deposition is carried out in an alternating manner for 200 cycles. Finally, electron gun 1 is turned on again to bombard the Y2O3 ceramic target doped with the first dopant ion. The deposition ends when the single layer thickness reaches 20nm, and a nano-layered Y2O3-YAG composite anti-etching coating is obtained.

[0028] The preparation method of the Y2O3 anti-etching coating in Comparative Example 1 includes the following steps: A ceramic substrate is provided, and the pretreatment steps for the ceramic substrate are the same as in Example 1; The pretreated ceramic substrate was fixed on the heated sample stage of the vacuum deposition chamber. High-purity argon gas was continuously introduced at a flow rate of 30 sccm. The gate valve was adjusted to stabilize the working gas pressure at 0.25 Pa. A negative bias of -120 V was applied, and the temperature was increased to 450 °C at a rate of 5 °C / min. The temperature was held for 30 min to form a uniform and stable deposition temperature field on the substrate surface. A water-cooled copper crucible filled with 99.99% high-purity Y2O3 ceramic target was placed in the vacuum deposition chamber. The electron gun emitters were all aligned with the center molten area of ​​the target material in the corresponding crucible. The electron gun was turned on to bombard the Y2O3 target material. The electron gun power was stabilized at 2.5 kW, and the deposition rate was 0.8 nm / s. The deposition was stopped when the thickness reached 6 μm, and a Y2O3 anti-etching coating was obtained.

[0029] The preparation method of the YAG anti-etching coating in Comparative Example 2 includes the following steps: A ceramic substrate is provided, and the pretreatment steps for the ceramic substrate are the same as in Example 1; The pretreated ceramic substrate was fixed on the heated sample stage of the vacuum deposition chamber. High-purity argon gas was continuously introduced at a flow rate of 30 sccm. The gate valve was adjusted to stabilize the working gas pressure at 0.25 Pa. A negative bias of -120 V was applied, and the temperature was increased to 450 °C at a rate of 5 °C / min. The temperature was held for 30 min to form a uniform and stable deposition temperature field on the substrate surface. A water-cooled copper crucible filled with 99.99% high-purity YAG ceramic target was placed in the vacuum deposition chamber. The electron gun emitters were all aligned with the center molten area of ​​the target material in the corresponding crucible. The electron gun was turned on to bombard the YAG target material. The electron gun power was stabilized at 2.2 kW, and the deposition rate was 0.5 nm / s. The deposition was stopped when the thickness reached 6 μm to obtain a YAG etch-resistant coating.

[0030] The preparation method of the Y2O3 / YAG composite anti-etching coating in Comparative Example 3 includes the following steps: 99.99% high-purity Y₂O₃ powder (average particle size 0.5-2 μm) and 99.99% high-purity YAG powder (average particle size 0.5-2 μm) were separately placed in corundum crucibles and kept at 800℃ for 3 hours in a muffle furnace to remove adsorbed water and trace organic impurities. After cooling to room temperature in the furnace, the powders were removed and mixed with YAG:Y₂O₃ at a molar ratio of 50:50. The mixtures were then placed in a polyurethane ball mill jar and dispersed in anhydrous ethanol (solid-liquid mass ratio 1:1.2). Zirconia balls (ball-to-material mass ratio 5:1) were used in a planetary ball mill at 300 r / min for 24 hours of continuous wet ball milling. The mixtures were then dried at 85℃ for 12 hours, lightly ground in an agate mortar, and passed through a 200-mesh standard sieve. 3% (w / w) of 5wt% (w / w) solution was added. PVA aqueous solution was used as a binder. After thorough grinding and mixing, it was passed through a 100-mesh sieve and filled into a steel mold. It was then pressed at 50 MPa for 30 seconds in a hydraulic press and placed in a cold isostatic press at 200 MPa for 60 seconds to prepare a green blank. The green blank was then placed in an air atmosphere muffle furnace and heated to 600℃ at 1℃ / min and held for 2 hours to remove the binder. The temperature was then increased to 1780℃ at 3℃ / min and sintered in air atmosphere for 4 hours. Subsequently, the temperature was decreased to 1000℃ at 2℃ / min and then naturally cooled to room temperature in the furnace. The surface was ground with a diamond wheel and the inner and outer circles were machined to the target dimensions to obtain the Y2O3 / YAG composite ceramic target. A ceramic substrate is provided, and the pretreatment steps for the ceramic substrate are the same as in Example 1; The pretreated ceramic substrate was fixed on the heated sample stage of the vacuum deposition chamber, and high-purity argon gas was continuously introduced at a flow rate of 30 sccm. The gate valve was adjusted to stabilize the working gas pressure at 0.25 Pa, and a negative bias of -120 V was applied. The temperature was increased to 450 °C at a rate of 5 °C / min and held for 30 min to form a uniform and stable deposition temperature field on the substrate surface. A water-cooled copper crucible filled with the Y2O3 / YAG composite ceramic target prepared above was placed in the vacuum deposition chamber. The electron gun emitters were all aligned with the central molten region of the target material in the corresponding crucible. The electron gun was turned on to bombard the Y2O3 / YAG composite ceramic target. The electron gun power was stabilized at 2.5 kW, the deposition rate was 0.8 nm / s, and the deposition was stopped when the thickness reached 6 μm to obtain a Y2O3 / YAG composite anti-etching coating.

[0031] Performance testing Coating porosity: The coating porosity was calculated using the gas permeation method. Before testing, the sample edges were sealed with epoxy resin, leaving only a set area of ​​the coating surface exposed to the test chamber. Based on the pressure difference method, 0.1 MPa of high-purity helium gas was introduced into one side of the test chamber, and a helium gas spectrometer leak detector was connected to the other side to measure the helium flow rate through the coating. Combining Darcy's law and the coating thickness, the effective through-porosity of the coating was calculated. The test results are shown in Table 1. Etching Resistance: Using a Radio Frequency Capacitive Coupled Plasma (RF Capacitive Coupled Plasma) etching machine manufactured by Chengdu Qixing Vacuum Coating Co., Ltd., the polished coating surface was exposed to a fluorine plasma containing CF4, Ar, and O2 as treatment gases for etching experiments at the set operating power. After a period of plasma etching, the height difference (etching depth) of the etched portion relative to the protected area was measured using a profilometer to reflect the etching resistance. The gas flow rate (sccm) was Ar:O2:CF4 = 45:5:40, the etching pressure was 20 Pa, the power was 250 W, and the time was 10 h. After etching, the etching depth h of each sample was measured, and the etching rate was calculated using the following formula: v = h / t; Where v is the etching rate (nm / min), h is the etching depth (nm), and t is the etching time (min); the detection results are shown in Table 1. Table 1: Statistical Table of Etch-Resistant Coating Performance Test Data for Examples 1-3 and Comparative Examples 1-3 Example 1 0.82 2990 5.2 Example 2 0.65 2420 4.1 Example 3 0.71 2610 4.5 Comparative Example 1 1.45 4920 8.5 Comparative Example 2 1.75 5770 10.2 Comparative Example 3 1.55 4370 7.1 As shown in Table 1, the nanolayered Y₂O₃-YAG composite anti-etching coating prepared in this invention exhibits excellent etching resistance, indicating that the nanolayered structure can effectively inhibit columnar crystal growth, reduce through-pores, and significantly improve etching resistance. Furthermore, the introduction of dopant ions further reduces the coating porosity and etching rate, demonstrating a synergistic effect between doping modification and the layered structure, further enhancing the coating's etching stability.

[0032] Depend on Figures 1 to 4 It can be seen that, Figure 1 and Figure 3 The images shown are laser confocal microscopy and atomic force microscopy images of the nanolayered Y2O3-YAG composite anti-etching coating prepared in Example 1 after 10 hours of etching. After 10 hours of fluorine plasma etching, the composite anti-etching coating still maintains a uniform and fine morphology with small overall undulation. No obvious intergranular etching trenches or large-area peeling pits were observed, which proves that the nanolayered structure effectively blocks the longitudinal penetration of the etching medium and the etching process is uniform and smooth. Figure 2 and Figure 4 The images shown are laser confocal microscopy and atomic force microscopy images of the Y2O3 anti-etching coating prepared in Comparative Example 1 after 10 hours of etching. After 10 hours of fluorine plasma etching, the surface of the pure Y2O3 coating forms a continuous network of etched grooves with significant unevenness and a substantial increase in roughness.

[0033] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0034] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A method for preparing a nano-layered Y₂O₃-YAG composite anti-etching coating, characterized in that, It includes at least the following preparation steps: Provide a ceramic substrate; Nanolayered Y2O3 and nanolayered YAG are alternately and cyclically deposited on one side of the ceramic substrate to obtain a nanolayered Y2O3-YAG composite anti-etching coating. Wherein, the nanolayered Y2O3-YAG composite anti-etching coating is located on the side closest to and furthest from the ceramic substrate, which is the nanolayered Y2O3. 3。 2. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The thickness of the nanolayered Y2O3-YAG composite anti-etching coating is 2-15 μm.

3. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The thickness of the nanolayered Y2O3 is 18-22 nm.

4. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The thickness of the nanolayered YAG is 8-12 nm.

5. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The nanolayered Y2O3 also contains a first dopant ion, and the first dopant ion is at least one of zirconium ion, scandium ion or gadolinium ion.

6. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 5, characterized in that, The doping amount of the first doped ion is 2-10 at.%.

7. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 6, characterized in that, The nanolayered YAG also contains a second doped ion, and the second doped ion is at least one of magnesium ion, silicon ion, lutetium ion or scandium ion.

8. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 7, characterized in that, The doping amount of the second doped ion is 0.5-10 at.%.

9. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The deposition rate of the nanolayered Y2O3 is 0.5-1.2 nm / s.

10. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The deposition rate of the nanolayered YAG is 0.3-0.8 nm / s.

11. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The deposition method is electron beam physical vapor deposition.

12. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 8, characterized in that, The doping method of the first doped ion and / or the second doped ion is any one of pre-alloyed evaporation source, multi-crucible co-evaporation, or ion-assisted deposition.

13. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The temperature of the ceramic matrix is ​​430-470℃.

14. The method for preparing the nanolayered Y₂O₃-YAG composite anti-etching coating according to claim 1, characterized in that, The ceramic matrix is ​​any one of alumina ceramic, aluminum nitride ceramic or silicon carbide ceramic, and the surface roughness Ra of the ceramic matrix is ​​≤0.05μm.

15. A nano-layered Y₂O₃-YAG composite anti-etching coating, characterized in that, It is prepared by the preparation method according to any one of claims 1-14.